If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = -3 + y Solving -4 = -3 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -4 + -1y = -3 + y + -1y Combine like terms: y + -1y = 0 -4 + -1y = -3 + 0 -4 + -1y = -3 Add '4' to each side of the equation. -4 + 4 + -1y = -3 + 4 Combine like terms: -4 + 4 = 0 0 + -1y = -3 + 4 -1y = -3 + 4 Combine like terms: -3 + 4 = 1 -1y = 1 Divide each side by '-1'. y = -1 Simplifying y = -1
| x+9.6=-12.4 | | 7x+6=5x+2x | | r^2+9r=3 | | -2x-10=2x+14 | | 12x(x)+11x=5 | | a^2x-2ax+x=a^2-1 | | 3(k-5)-2(k+1)-13=-23 | | 11n^2=-8 | | 3.5x^2-5x-2.5=0 | | 6x=0.125 | | -3(6n+4)+5=-97 | | 2x+6=47 | | 3x+2-2x=x+2 | | -10+3y=-30 | | 4c^2+4x-8=1 | | 5x-5=11x+2-1 | | (X+3)*(x-7)=(x-3)2 | | 2x+5=4+2x+1 | | 5+13=-4 | | 3x-8x=16 | | x/5+5=3 | | Y=4x+-1 | | 5g+9=17 | | 5.9=x^3-3x+4 | | (x-3)*2+2x=14 | | 6j-3j-2j-1=16 | | 14c-c+3c-13c+4c=14 | | .25+y+z=3.00 | | A(4)=3.14r*3.14r | | 14b+-20b=18 | | 140=(x+5)(2x+4) | | 7y^2-3y+5y^2-4y= |